Cell-free expression with the toxic amino acid canavanine. Issue 17 (1st September 2015) - Worst, Emanuel G.; Exner, Matthias P.; De Simone, Alessandro; Schenkelberger, Marc; Noireaux, Vincent; Budisa, Nediljko; Ott, Albrecht
Graphical abstract The toxic amino acid canavanine is a natural allelochemic agent and analogous to arginine. It can be incorporated very efficiently into recombinant proteins by using cell-free expression.